2020
DOI: 10.1002/cssc.202002700
|View full text |Cite
|
Sign up to set email alerts
|

Green Preparation of Thin Films of Polybenzimidazole on Flat and Hollow Fiber Supports: Application to Hydrogen Separation

Abstract: This work shows the preparation of thin films, with thickness from 70 nm to 1 μm, of meta‐polybenzimidazole (m‐PBI) on polyimide P84 supports. Ethanolic solutions of m‐PBI were used to coat flat and hollow fiber supports of asymmetric P84 with m‐PBI in a process where the coating and drying was performed at room temperature. A solution of NaOH in EtOH allowed the dissolution of the m‐PBI powder, providing the perfect coating solution to build thin films of m‐PBI without damaging the polymeric support. It also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…230,231 HFMs. 81,82,109,132,167,168,[232][233][234][235][236][237] Key achievements and major breakthroughs are highlighted as follows. Kumbharkar et al fabricated m-PBI HFMs using DMAc/water as a bore uid and water as an external coagulant and then coated them with 6F-PBI to seal the defects for H 2 /CO 2 separation at 100-400 C. 81 It was found that the bore uid chemistry played an important role in determining membrane morphology, gas separation performance and mechanical strength.…”
Section: Gas Separation For H 2 /Co 2 Separation At Elevated Temperat...mentioning
confidence: 99%
“…230,231 HFMs. 81,82,109,132,167,168,[232][233][234][235][236][237] Key achievements and major breakthroughs are highlighted as follows. Kumbharkar et al fabricated m-PBI HFMs using DMAc/water as a bore uid and water as an external coagulant and then coated them with 6F-PBI to seal the defects for H 2 /CO 2 separation at 100-400 C. 81 It was found that the bore uid chemistry played an important role in determining membrane morphology, gas separation performance and mechanical strength.…”
Section: Gas Separation For H 2 /Co 2 Separation At Elevated Temperat...mentioning
confidence: 99%
“…Polybenzimidazoles (PBIs) type polymers are known for their high thermochemical stabilities and excellent mechanical properties. [1][2][3][4][5][6][7][8][9] They have been found useful in applications ranging from flame-resistant fabrics to aerospace materials and fuel cell membranes. [10][11][12][13][14][15][16] Fully aromatic poly[2,2-(m-phenylene)-5,5-bibenzimidazole] or meta-PBI (m-PBI) (Scheme 1) is the most common commercially available PBI polymer.…”
Section: Introductionmentioning
confidence: 99%
“…High intrinsic H 2 selectivity over larger gas molecules, such as CO 2 , N 2 , and CH 4 , was demonstrated with PBI film membranes prepared using flat and hollow polyamide P84 fibers as a support material. [ 8 ] PBI has gained great interest also as a membrane material in vanadium redox flow batteries where ion‐selectivity for vanadium was obtained with a thin layer of PBI polymer. [ 22 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polybenzimidazole (PBI) is a promising candidate for the separation of a pre-combustion gas mixture (H 2 /CO 2 ) due to its good chemical resistance, high thermal stability, high intrinsic H 2 /CO 2 selectivity as well as impressive compression strength [8][9][10]. Besides, recently, the green processability of PBI in ethanol has been demonstrated to produce highly selective coatings of this polymer both on flat and hollow fibre (HF) polymeric supports [11].…”
Section: Introductionmentioning
confidence: 99%